Preparation method and application of phenanthroline iron (II) coordination carbon-based catalyst
By preparing Fe/N-CS catalysts, the problems of ion leakage and uneven distribution of metal catalysts in the prior art are solved, efficient activation of persulfate and efficient degradation of tetracycline are achieved, and short degradation cycles, low cost and good anti-interference ability are achieved.
Patent Information
- Application Number
- CN202311259271.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-09-27
AI Technical Summary
The prior art has the risk of ion leakage when using metal catalysts, making it difficult to effectively form Fe-Nx coordination and uniform distribution on the carbon matrix, affecting the efficient activation of persulfate and the degradation efficiency of tetracycline.
FeCl2·4H2O and 1,10-phenanthroline were reacted at room temperature, chitosan and an acidic solution were added to form a hydrogel, and the Fe/N-CS catalyst was prepared by freeze-drying and calcining, and the iron metal was fully supported in the reduced graphene oxide material.
The efficient activation of persulfate is achieved, which significantly improves the degradation efficiency of tetracycline, has a short degradation cycle and is cheap, and the catalyst has strong anti-interference ability to various ions and has good cycle durability.
Smart Images

Figure CN119733540A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water pollution treatment in environmental engineering, and in particular relates to a preparation method and application of a phenanthroline iron (II) coordinated carbon-based catalyst. Background Art
[0002] There are many kinds of antibiotics, which are gradually widely used in animal husbandry, aquaculture and medical industries. Among them, tetracycline (TC) is the most widely used because of its low cost, low toxicity and broad-spectrum activity. However, the use and abuse of tetracycline has caused 70% of tetracycline to be released into the environment as metabolites or even in its original state, and it has been frequently detected in water bodies in recent years. Tetracycline not only causes serious pollution to groundwater, but also leads to the emergence of drug-resistant bacteria, posing a threat to human health and safety. Therefore, it is of great significance to develop an effective method to remove TC from water.
[0003] At present, tetracycline water pollution treatment technologies mainly include adsorption, biodegradation, ion exchange, membrane filtration and advanced oxidation processes (AOPs). Among them, persulfate-based AOPs can activate peroxymonosulfate (PMS, molecular formula HSO 5 - ) produces a variety of strong oxidizing active groups, inducing the breaking of chemical bonds of organic matter, causing it to degrade into small molecules or even completely mineralize into inorganic molecules. It has significant advantages in the degradation of TC in wastewater and is regarded as the most promising water treatment technology.
[0004] The activation methods of persulfate mainly include the input of external energy (such as heating, ultraviolet and ultrasound), alkali activation, transition metal activation and other activation methods. Among them, the catalyst is conducive to the activation of PMS to produce highly active SO4 ·- , which has been widely studied. However, the use of some metal catalysts (such as Co, Mn and Cu, etc.) has the risk of ion leakage, which may cause secondary pollution of water bodies. Recently, new Fe-NC hybrid catalysts have been considered as promising candidates for PMS activation. 3 The Fe / N co-doped biochar (Fe-NC) material prepared by simple pyrolysis of a mixture of cyanamide and dicyandiamide achieved a larger specific surface area and a higher degree of defects. Fe-NC can efficiently activate PMS to degrade BPA, and its reaction rates are 37.07 and 6.04 times that of the BC / PMS and N-BC / PMS systems, respectively. The Fe-NC hybrid catalyst adjusts the sp 2The charge distribution of the hybrid carbon framework can be improved, and the redox cycle of the loaded Fe species can be promoted, thereby improving the activation efficiency. However, due to the heterogeneity of the physical mixing of the raw materials, it may be difficult to effectively form Fe-N x coordination and uniform distribution on the carbon matrix, it is necessary to develop a facile and feasible strategy to prepare Fe-NC catalysts for efficient activation of PMS. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of the prior art, the present invention provides a method for preparing a phenanthroline iron (II) coordinated carbon-based catalyst with a simple method and high degradation efficiency and its application. The specific contents are as follows:
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing a phenanthroline iron (II) coordinated carbon-based catalyst capable of efficiently activating persulfate comprises the following steps:
[0008] Step S1, using FeCl 2 ·4H 2 O was dissolved in water, 1,10-phenanthroline was added and stirred continuously at room temperature for 0-1 h.
[0009] Step S2, uniformly dispersing the solution in step S1, adding chitosan (CS) and acid solution, and fully dissolving to form a uniform viscous solution
[0010] Step S3, continuously stirring the viscous solution in step S2, and slowly dripping the sodium hydroxide solution until the hydrogel is completely formed.
[0011] Step S4, repeatedly washing the material in step S3 with water until a neutral pH value is reached,
[0012] Step S5, freeze-drying the material in step S4.
[0013] Step S6, calcining the material in step S5 at 500-1000° C. under inert gas protection to obtain Fe / N-CS. By adopting this technical solution, iron metal is fully loaded in the reduced graphene oxide material, and the obtained material has a high catalytic efficiency for persulfate. The catalyst has the advantages of simple preparation process, low cost, short degradation cycle, etc.
[0014] The above method is further improved, wherein the FeCl 2 ·4H 2 The mass of O is 0-0.5 g, and the mass of 1,10-phenanthroline is 0-1 g.
[0015] The above method is further improved, in step S2, the mass of chitosan (CS) is 0-0.5 g, the acidic solution includes acetic acid, citric acid, phosphoric acid solution, and the volume fraction of the acidic solution is 0-10%.
[0016] The above method is further improved, wherein the concentration of the sodium hydroxide solution in step S3 is 0-2M and the volume is 1-1000ml.
[0017] The above method is further improved, wherein the freeze drying in step S5 includes freezing in a -80°C refrigerator for 1-24 hours and drying in a vacuum freeze dryer at -40°C for 1-24 hours.
[0018] The above method is further improved, wherein the calcination temperature in step S6 is 500-1000°C, and after reaching the highest calcination temperature, it is maintained for 1-3 hours, and the heating program is set to a heating rate of 5-15°C·min -1 .
[0019] The above method is further improved, wherein the inert gas in step S6 is argon or nitrogen.
[0020] The invention discloses the application of a phenanthroline iron (II) coordinated carbon-based catalyst as described above, which is used for activating persulfate to degrade tetracycline and tetracycline residues in sewage and wastewater. Preferably, the persulfate comprises one or a mixture of two of potassium persulfate, ammonium persulfate and potassium hydrogen persulfate composite salt.
[0021] The invention also discloses a method for degrading tetracycline antibiotics by using activated persulfate advanced oxidation technology, wherein a solution containing tetracycline antibiotics is mixed with persulfate, and then the phenanthroline iron (II) coordinated carbon-based catalyst is added to perform full degradation.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] First, the present invention utilizes Fe 2+ and phen as FeN x The precursor of the site was modified by chemical cross-linking reaction of chitosan (CS) to quickly prepare a phenanthroline iron (II) coordinated carbon-based catalyst, which has many significant advantages. A variety of Fe / N-CS catalysts were prepared at different pyrolysis temperatures. SEM, Raman and BET results show that with the increase of pyrolysis temperature, the material has higher carbon defects and larger specific surface area. 3 C and Fe 3The formation of N sites can provide a large number of active sites in the reaction, which in turn helps to improve the catalytic performance. This provides a facile strategy for the synthesis of advanced oxidation catalysts and promotes further research in the field of persulfate advanced oxidation.
[0024] Second, in the present invention, chitosan (CS) is a hydrogel adsorbent material widely used in heavy metal pollution in the environment. Due to the network structure of the polymer itself, the three-dimensional porous structure characteristics and large specific surface area can produce more adsorption sites, greatly enhancing the adsorption capacity of the hydrogel for heavy metal ions. The freeze-drying method not only retains the three-dimensional (3D) porous structure, but also can achieve the effect of fixing the metal precursor with a certain atomic ratio during the solvent sublimation process. The combination of the two inhibits the leakage of iron ions and greatly improves the catalytic ability of Fe / N-CS.
[0025] Third, the Fe / N-CS catalyst activated peroxymonosulfate to degrade tetracycline wastewater. When the peroxymonosulfate solution was 0.5 mM and the Fe / N-CS catalyst was 0.05 g·L -1 , Tetracycline solution = 20 mg·L -1 Under the conditions of temperature = 25℃, tetracycline can be efficiently degraded within 20 minutes.
[0026] Fourth, by using the technical solution of the present invention, the degradation rate of tetracycline in the Fe / N-CS catalyst in the activated peroxymonosulfate system increases with the increase in the catalyst dosage.
[0027] Fifth, by adopting the technical solution of the present invention, the Fe / N-CS catalyst has strong anti-interference ability to various ions, strong cycle durability, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are the SEM and TEM images of Example 1 of the present invention.
[0029] Figure 2 It is the X-ray diffraction spectrum of the catalyst of Example 2 of the present invention and Comparative Examples 1, 2, and 3.
[0030] Figure 3 It is the Raman graph of the catalyst of Example 2 of the present invention and Comparative Examples 1, 2, and 3.
[0031] Figure 4 is the N of the catalysts in Example 2 of the present invention and Comparative Examples 1, 2, and 3 2 Adsorption–desorption isotherms.
[0032] Figure 5 It is a tetracycline degradation curve diagram of the catalyst of Example 4 of the present invention.
[0033] Figure 6 It is a tetracycline degradation curve diagram of the Fe / N-CS-4 / PMS system of Example 4 of the present invention at different catalyst dosages. DETAILED DESCRIPTION
[0034] Below in conjunction with the drawings and Examples, the specific embodiments of the present invention are described in further detail. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Any parameters and data shown in the present invention are not limited to accurate ranges or values, but should be understood to include parameters and data close to these ranges or values.
[0035] Example 1
[0036] Take a certain mass (M = 0.05-0.1g) of FeCl 2 ·4H 2 O was dissolved in 1-100 mL of deionized water, and then 1,10-phenanthroline with a mass ratio (Fe:Phen) of 1:2-1:10 was added and stirred continuously at room temperature for 30 minutes. Then 0.2 g of CS powder was evenly dispersed in the above solution and 2% volume acetic acid was added to fully dissolve it to form a uniform viscous solution. Under continuous stirring, 1M NaOH solution was slowly added dropwise to the above viscous solution until a hydrogel was completely formed. After the gelation process was completed, the hydrogel was repeatedly rinsed with deionized water until a neutral pH value was reached. Subsequently, the gel was placed in a -80°C refrigerator and frozen overnight, and then a vacuum freeze dryer was used to remove all moisture. Finally, the above sample was placed in a tubular furnace and refrigerated at 5°C min in an Ar atmosphere. -1 The temperature was raised to the specified temperature (800°C) at a rate of and maintained for calcination for 2 h to obtain Fe / N-CS-800 and (Fe / N-CS-0.06), respectively.
[0037] Comparative Example 1
[0038] Take a certain mass (M = 0.05-0.1g) of FeCl 2 ·4H 2O was dissolved in 1-100 mL of deionized water, and then 1,10-phenanthroline with a mass ratio (Fe:Phen) of 1:2-1:10 was added and stirred continuously at room temperature for 30 minutes. Then 0.2 g of CS powder was evenly dispersed in the above solution and 2% volume acetic acid was added to fully dissolve it to form a uniform viscous solution. Under continuous stirring, 1M NaOH solution was slowly added dropwise to the above viscous solution until a hydrogel was completely formed. After the gelation process was completed, the hydrogel was repeatedly rinsed with deionized water until a neutral pH value was reached. Subsequently, the gel was placed in a -80°C refrigerator and frozen overnight, and then a vacuum freeze dryer was used to remove all moisture. Finally, the above sample was placed in a tubular furnace and refrigerated at 5°C min in an Ar atmosphere. -1 The temperature was raised to the specified temperature (600°C) at a rate and kept calcined for 2h to obtain Fe / N-CS-600 respectively.
[0039] Comparative Example 2
[0040] Take a certain mass (M = 0.05-0.1g) of FeCl 2 ·4H 2 O was dissolved in 1-100 mL of deionized water, and then 1,10-phenanthroline with a mass ratio (Fe:Phen) of 1:2-1:10 was added and stirred continuously at room temperature for 30 minutes. Then 0.2 g of CS powder was evenly dispersed in the above solution and 2% volume acetic acid was added to fully dissolve it to form a uniform viscous solution. Under continuous stirring, 1M NaOH solution was slowly added dropwise to the above viscous solution until a hydrogel was completely formed. After the gelation process was completed, the hydrogel was repeatedly rinsed with deionized water until a neutral pH value was reached. Subsequently, the gel was placed in a -80°C refrigerator and frozen overnight, and then a vacuum freeze dryer was used to remove all moisture. Finally, the above sample was placed in a tubular furnace and refrigerated at 5°C min in an Ar atmosphere. -1 The temperature was raised to the specified temperature (700°C) at a rate of and maintained for calcination for 2h to obtain Fe / N-CS-700 respectively.
[0041] Comparative Example 2
[0042] Take a certain mass (M = 0.05-0.1g) of FeCl 2 ·4H 2O was dissolved in 1-100 mL of deionized water, and then 1,10-phenanthroline with a mass ratio (Fe:Phen) of 1:2-1:10 was added and stirred continuously at room temperature for 30 minutes. Then 0.2 g of CS powder was evenly dispersed in the above solution and 2% volume acetic acid was added to fully dissolve it to form a uniform viscous solution. Under continuous stirring, 1M NaOH solution was slowly added dropwise to the above viscous solution until a hydrogel was completely formed. After the gelation process was completed, the hydrogel was repeatedly rinsed with deionized water until a neutral pH value was reached. Subsequently, the gel was placed in a -80°C refrigerator and frozen overnight, and then a vacuum freeze dryer was used to remove all moisture. Finally, the above sample was placed in a tubular furnace and refrigerated at 5°C min in an Ar atmosphere. -1 The temperature was raised to the specified temperature (700°C) at a rate of 200 °C and kept calcined for 2 h to obtain Fe / N-CS-700.
[0043] Comparative Example 3
[0044] Take a certain mass (M = 0.05-0.1g) of FeCl 2 ·4H 2 O was dissolved in 1-100 mL of deionized water, and then 1,10-phenanthroline with a mass ratio (Fe:Phen) of 1:2-1:10 was added and stirred continuously at room temperature for 30 minutes. Then 0.2 g of CS powder was evenly dispersed in the above solution and 2% volume acetic acid was added to fully dissolve it to form a uniform viscous solution. Under continuous stirring, 1M NaOH solution was slowly added dropwise to the above viscous solution until a hydrogel was completely formed. After the gelation process was completed, the hydrogel was repeatedly rinsed with deionized water until a neutral pH value was reached. Subsequently, the gel was placed in a -80°C refrigerator and frozen overnight, and then a vacuum freeze dryer was used to remove all moisture. Finally, the above sample was placed in a tubular furnace and refrigerated at 5°C min in an Ar atmosphere. -1 The temperature was raised to the specified temperature (900°C) at a rate of 100 °C and kept calcined for 2 h to obtain Fe / N-CS-900.
[0045] Example 2
[0046] Take 0.2g CS powder and evenly disperse it in the above solution and add 2% volume ratio of acetic acid to fully dissolve it to form a uniform viscous solution. Under continuous stirring, slowly add 1M NaOH solution to the above viscous solution until the hydrogel is completely formed. After the gelation process is completed, the hydrogel is repeatedly rinsed with deionized water until a neutral pH value is reached. Subsequently, the gel is placed in a -80℃ refrigerator and frozen overnight, and then a vacuum freeze dryer is used to remove all moisture. Finally, the above sample is placed in a tubular furnace and heated at 5℃ min in an Ar atmosphere. -1 The temperature was raised to 800 °C at a rate of 1.5 ℃ and kept for calcination for 2 h to obtain N-CS.
[0047] in Figure 1 SEM and TEM images of Fe / N-CS-800 prepared by the preparation method provided by the present invention. As can be seen from the figure, the catalysts all present a loose and porous layered structure, and metal nanoparticles are evenly embedded on the surface. As the pyrolysis temperature increases, the surface of the Fe / N-CS catalyst gradually becomes rougher, and the distribution of metal particles on the surface becomes more obvious. This may be because high temperature causes more defects in the carbon structure, which helps to expose more active sites, thereby improving the catalytic performance. Among them, Fe / N-CS in Comparative Example 1 has fewer metal particles attached, and cannot provide enough catalytic active sites, resulting in weak catalytic performance. The Fe / N-CS-900℃ structure in Comparative Example 3 is more distorted and wrinkled, and is partially coated with more particles, agglomeration occurs, and the catalytic effect also decreases slightly. In Example 1, the surface of Fe / N-CS-800 is loaded with ordered, highly dispersed iron nanoparticles, which is conducive to the full exposure of catalytic sites, thereby having higher catalytic performance. Combined with the TEM image and energy spectrum analysis of Fe / N-CS-800, it can be seen that the Fe nanoparticles are evenly embedded in the external carbon substrate material. The lattice measurement shows that the lattice spacing of the outer carbon layer structure is 0.324nm, corresponding to the (002) crystal plane of graphite C, and the lattice spacing of the inner nanoparticles is 0.201nm, which is similar to Fe 3 The (031) crystal plane of C matches.
[0048] Example 3
[0049] Take a certain mass (M = 0.01-0.05g) of FeCl 2 ·4H 2 O was dissolved in 1-100 mL of deionized water, and then 1,10-phenanthroline with a mass ratio (Fe:Phen) of 1:2-1:10 was added and stirred continuously at room temperature for 30 minutes. Then 0.2 g of CS powder was evenly dispersed in the above solution and 2% volume acetic acid was added to fully dissolve it to form a uniform viscous solution. Under continuous stirring, 1M NaOH solution was slowly added dropwise to the above viscous solution until a hydrogel was completely formed. After the gelation process was completed, the hydrogel was repeatedly rinsed with deionized water until a neutral pH value was reached. Subsequently, the gel was placed in a -80°C refrigerator and frozen overnight, and then a vacuum freeze dryer was used to remove all moisture. Finally, the above sample was placed in a tubular furnace and refrigerated at 5°C min in an Ar atmosphere. -1 The temperature was raised to the specified temperature (800°C) at a rate of and maintained for calcination for 2 h to obtain Fe / N-CS-0.01-800.
[0050] Example 4
[0051] This example describes the effect of catalyst-activated peroxymonosulfate on tetracycline wastewater at different pyrolysis temperatures in the Fe / N-CS / PMS system.
[0052] The Fe / N-CS catalyst is used to activate persulfate to degrade tetracycline. The specific process is as follows: at room temperature of 25°C, 100 mL of 20 mg·L -1 The tetracycline solution was poured into a 250 mL beaker, followed by the addition of 0.5 mM persulfate and 0.05 g·L -1 Fe / N-CS catalyst, use a 350rpm stirring paddle to stir the mixed solution and start the degradation experiment. Draw 1mL of the reaction solution at a certain time interval, immediately add 1mL of ethanol quencher, shake well to quench the free radicals, and terminate the degradation experiment. After adding deionized water to dilute the mixed solution to a certain volume, filter it with a polytetrafluoroethylene filter membrane with a pore size of 0.22μm, and then determine the concentration of tetracycline in the mixed solution by high performance liquid chromatography. All experiments were repeated three times in parallel under the same conditions to prevent excessive errors.
[0053] like Figure 6 It can be seen that the addition of PMS alone only achieved a TC degradation rate of 12.8%, and the reaction rate was 0.015min -1 , indicating that the oxidation performance of PMS is very limited without activation. In the N-CS / PMS system, the degradation efficiency of TC is 29.5%. With the increase of pyrolysis temperature, the efficiency of TC degradation in the Fe / N-CS / PMS system increased significantly from 44.3% (Fe / N-CS-600) to 91.2% (Fe / N-CS-900), and the corresponding reaction rate also increased from 0.052min -1 Increase to 0.210min -1 On the one hand, high temperature helps to form a larger specific surface area, providing a reaction platform for the attachment of PMS and the degradation of pollutants; on the other hand, high temperature promotes the formation of more carbon defects, which helps to expose active sites and thus improve the catalytic performance. However, the degradation efficiency of TC increased by only 0.5% after the preparation temperature was increased from 800℃ to 900℃, which may be due to the excessively high temperature causing some FeN x The sites are destroyed, thus inhibiting the further improvement of its catalytic performance. Considering the economic cost and degradation effect comprehensively, 800℃ was selected as the optimal temperature for preparing Fe / N-CS catalyst.
[0054] Figure 2The crystal structure and composition of Fe / N-CS catalysts prepared at different temperatures are shown in Figure 2. All catalysts have a characteristic peak at 26.4°, corresponding to the (002) crystal plane of graphite C (JCPDS#41-1487), indicating that the carbon substrate is a graphene-like structure. At the same time, Fe / N-CS has diffraction peaks at 37.8°, 39.8°, 40.6°, 45.0°, 48.6° and 49.1°, which are respectively 3 The (210), (002), (201), (031), (131) and (221) crystal planes of C match each other (JCPDS#85-1317), which proves that the catalyst is mainly composed of Fe 3 C is the main component, which is consistent with the TEM lattice measurement data mentioned above. In addition, with the increase of pyrolysis temperature, Fe 3 The intensity of the (031) crystal plane of C also increases, indicating that high temperature is conducive to its growth. In addition, there are obvious characteristic peaks at 43.7° and 57.5°, representing Fe 3 The (111) and (112) crystal planes of N (JCPDS#49-1663) further prove the formation of FeNx sites.
[0055] Figure 3 The Raman graphs of Fe / N-CS catalysts at different temperatures are shown, which are used to study the defects and graphitization degree of carbon materials. -1 and 1585cm -1 The two characteristic peaks near the carbon belong to the D band (disordered graphitic carbon) and the G band (sp 2 Hybridized graphite carbon), the ratio of the two intensities (I D / I G ) size is usually positively correlated with the degree of defects in carbon materials. The I D / I G The values are 0.93, 0.95, 0.97, and 0.99, respectively, indicating that high temperature helps the material to form more lattice defects, which may be attributed to the reconstruction of the carbon matrix.
[0056] Figure 4 The N of Fe / N-CS catalysts prepared at different temperatures is shown in Figure 2 2 Adsorption-desorption isotherms and pore size distribution. All samples show typical type IV isotherms and H4 type hysteresis curves in the medium and high pressure range, proving that micropores and mesopores coexist in Fe / N-CS materials. Studies have shown that FeN xThe sites are mainly distributed in the microporous structure, so the presence of more micropores in the Fe-NC material can provide more anchoring space for the active site; and for the catalytic reaction, the mesoporous structure is conducive to accelerating the mass transfer process between the oxidation substrate and the catalyst, thereby improving the catalytic activity. In addition, with the increase of the pyrolysis temperature, the height of the isotherm increases accordingly. This shows that high temperature helps to increase the specific surface area of the material. Fe / N-CS-900 has the largest specific surface area and average pore size, reaching 531.879m 2 g -1 and 0.579nm.
[0057] Figure 5 As shown in Figure 2, with the increase of pyrolysis temperature, the efficiency of TC degradation by the Fe / N-CS / PMS system increased significantly from 44.3% (Fe / N-CS-600) to 91.2% (Fe / N-CS-900), and the corresponding reaction rate also increased from 0.052 min -1 Increase to 0.210min -1 On the one hand, high temperature helps to form a larger specific surface area, providing a reaction platform for the attachment of PMS and the degradation of pollutants; on the other hand, high temperature promotes the formation of more carbon defects, which helps to expose active sites and thus improve the catalytic performance. However, the degradation efficiency of TC increased by only 0.5% after the preparation temperature was increased from 800℃ to 900℃, which may be due to the excessively high temperature causing some FeN x The sites are destroyed, thus inhibiting the further improvement of its catalytic performance. Considering the economic cost and degradation effect comprehensively, 800℃ was selected as the optimal temperature for preparing Fe / N-CS catalyst.
[0058] The present invention is described in detail above. Those skilled in the art can implement the present invention by appropriately changing the conditions and routes without departing from the scope of the present invention. Although the embodiments of the present invention have been described in detail, the embodiments of the present invention are not limited to the embodiments given, and all similar changes, substitutions and modifications are considered to be within the scope of the technical protection of the present invention.
Claims
1. A preparation method and application of a phenanthroline iron (II) coordinated carbon-based catalyst, comprising the following steps: Step 1, dissolve FeCl2·4H2O in water, add 1,10-phenanthroline and stir continuously at room temperature for 0-1h. Step 2: Evenly disperse the solution in step 1, add chitosan (CS) and acid solution, and fully dissolve to form a uniform viscous solution. Step 3, the viscous solution in step 2 is continuously stirred, and the sodium hydroxide solution is slowly dripped into the solution until the hydrogel is completely formed. Step 4: Rinse the material in step 3 repeatedly with water until a neutral pH value is reached. Step 5, freeze-drying the material in step 4. Step 6, calcining the material in step 5 at 500-1000° C. under inert gas protection to obtain Fe / N-CS.
2. A method for preparing a phenanthroline iron (II) coordinated carbon-based catalyst (Fe / N-CS) according to claim 1 and its application, characterized in that: The mass of FeCl2·4H2O in step 1 is 0-0.5 g, which is dissolved in 0-100 ml of water, and the mass of 1,10-phenanthroline is 0-1 g.
3. A method for preparing a phenanthroline iron (II) coordinated carbon-based catalyst (Fe / N-CS) according to claim 1 and its application, characterized in that: In step 2, the mass of chitosan (CS) is 0-0.5 g, the acidic solution includes acetic acid, citric acid, and phosphoric acid solution, and the volume fraction of the acidic solution is 0-10%.
4. A method for preparing a phenanthroline iron (II) coordinated carbon-based catalyst (Fe / N-CS) according to claim 1 and its application, characterized in that: The sodium hydroxide solution in step 3 has a concentration of 0-2M and a capacity of 1-1000ml.
5. The preparation method and application of a phenanthroline iron (II) coordinated carbon-based catalyst (Fe / N-CS) according to claim 1, characterized in that: The freeze drying in step 5 includes freezing in a -80°C refrigerator for 1-24 hours and drying in a vacuum freeze dryer at -40°C for 1-24 hours.
6. The preparation method and application of a phenanthroline iron (II) coordinated carbon-based catalyst (Fe / N-CS) according to claim 1, characterized in that: The calcination temperature in step 6 is 500-1000°C, and the temperature is maintained for 1-3 hours after reaching the highest calcination temperature. The heating rate is set at 5-15°C·min -1 .
7. The preparation method and application of a phenanthroline iron (II) coordinated carbon-based catalyst (Fe / N-CS) according to claim 1, characterized in that: The inert gas in step 6 is argon or nitrogen.
8. The preparation method and application of a phenanthroline iron (II) coordinated carbon-based catalyst according to claim 1, characterized in that: Used to activate persulfate to degrade antibiotics and antibiotic residues in wastewater.
Citation Information
Patent Citations
Application of porous FeCo-N / C carbon nanomaterial in selective reduction of p-nitrophenol
CN115318324A
Method for degrading organic pollutants by activating peroxymonosulfate with environment-interference-resistant Fe-coated N-CNs composite catalytic material
CN115677010A
Method for manufacturing oxygen reduction catalyst
JP2015044153A